Visual analysis of information world maps: An exploration of four methods. (June 2020) - Greyson, Devon; O'Brien, Heather; Shankar, Saguna
Information researchers increasingly use participatory, arts-based methods to better understand the social contexts of individuals and populations. However, it remains rare to engage in qualitative analysis of the resulting visual artefacts. This article explores approaches to analysing visual media generated through a specific arts-based method, information world mapping (IWM), an interdisciplinary draw-and-talk technique that elicits data about individuals' social information worlds. Here, we test four approaches to analysing visual media generated through IWM: directed qualitative content analysis (QCA), compositional interpretation, conceptual analysis and visual discourse analysis using situational analysis (SA). QCA was effective in creating an overview of participants' information practices, yet raised concern regarding interpretive bias. Using an inductive taxonomy for compositional interpretation, we identified genre conventions for IWMs. Conceptual analysis resulted primarily in a reflection of the research procedures and epistemology. SA, while time-consuming, generated a large amount of rich data, including discourses and power relations that were not identified in previous analysis of textual data. In a reversal of our previous stance that cautioned against IWM analysis, we encourage other researchers to consider integrated or secondary visual analysis of IWMs.